2006
DOI: 10.1128/iai.74.3.1643-1648.2006
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Laminin γ-1 Gene Blocks Trypanosoma cruzi Infection

Abstract: It is thought that Trypanosoma cruzi, the protozoan that causes Chagas' disease, modulates the extracellular matrix network to facilitate infection of human cells. However, direct evidence to document this phenomenon is lacking. Here we show that the T. cruzi gp83 ligand, a cell surface trans-sialidase-like molecule that the parasite uses to attach to host cells, increases the level of laminin ␥-1 transcript and its expression in mammalian cells, leading to an increase in cellular infection. Stable RNA interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 20 publications
0
64
0
7
Order By: Relevance
“…T. cruzi presents surface molecules, such as gp85 (Marino et al, 2003) and gp83 (Nde et al, 2006) glycoproteins that bind to laminin and fibronectin (Marino et al, 2003;Nde et al, 2006) and to sulfated glycosamineglicans such as heparan sulphate (Lima et al, 2002). We have previously shown that the parasite induces a decrease of glycosylated molecules of the basal lamina, specifically laminin and heparan sulphate (Duaso et al, 2010;Duaso et al 2011b).…”
Section: Trypanosoma Cruzi Interaction With the Villous Stromamentioning
confidence: 99%
See 1 more Smart Citation
“…T. cruzi presents surface molecules, such as gp85 (Marino et al, 2003) and gp83 (Nde et al, 2006) glycoproteins that bind to laminin and fibronectin (Marino et al, 2003;Nde et al, 2006) and to sulfated glycosamineglicans such as heparan sulphate (Lima et al, 2002). We have previously shown that the parasite induces a decrease of glycosylated molecules of the basal lamina, specifically laminin and heparan sulphate (Duaso et al, 2010;Duaso et al 2011b).…”
Section: Trypanosoma Cruzi Interaction With the Villous Stromamentioning
confidence: 99%
“…The increase of laminin expression could be induced by the parasite, which needs to attach to ECM molecules for cellular invasion (Marino et al, 2003). The silencing of the laminin gene inhibits cell invasion of the T. cruzi (Nde et al, 2006). The parasitic protease cruzipain degrades collagen IV and fibronectin, exposing epitopes to which T. cruzi binds (Scharfstein and Morrot, 1999), facilitating also the binding to laminin and consequently the cell invasion.…”
Section: Trypanosoma Cruzi Interaction With the Villous Stromamentioning
confidence: 99%
“…Since this trypanosome ligand is released from the parasite by the action of a parasite PLC in order to signal macrophages and non-phagocytic cells, special attention has been given to its description and characterization. Previous reports have shown that the T. cruzi surface gp83 (45,(50)(51)(52) is expressed only in invasive trypomastigotes (48), is more expressed in highly than weakly infective trypomastigote clones (46) and that blocking this molecule with antigp83 antibodies reduces trypanosome binding and invasion (48). Purified soluble gp83, from PLC-treated T. cruzi trypomastigote membranes, binds to myoblasts, fibroblasts and macrophages to mediate trypanosome entry (62).…”
Section: Trans-sialidases and Trans-sialidase Like Moleculesmentioning
confidence: 99%
“…The candidate trypomastigote ligands for structural and atomic analysis are TS, TS-like molecules (36,53,57), mucins (58), heparin binding protein (59), and surface casein kinase II substrates (60) that bind to nonphagocytic cells, kinases and to extracellular matrix proteins (52)(53)(54)(55)(56)(57)(58)(59)(60)(61) and to host cell receptors on non-phagocytic cells in order to invade them (52)(53)(54)(55)(56)(57). It is thought that trypanosome trans-sialidases transfer sialic acids to trypanosome mucins and serve as acceptors of sialic acids during infection.…”
Section: Trans-sialidases and Trans-sialidase Like Moleculesmentioning
confidence: 99%
See 1 more Smart Citation